Chemical alteration of carotene biosynthesis in Phycomyces blakesleeanus and mutants. - Lee, T C (1975)
The effects of diphenylamine, dimethyl sulfoxide, streptomycin, AMO-1618, and beta-ionone on the carotene composition of a wild-type and three mutant strains of Phycomyces blakesleeanus have been examined. Diphenylamine increased the phytoene and phytofluene concentrations of all strains while reducing the levels of the color carotenes. Dimethyl sulfoxide reduced the concentration of both cyclic and acyclic carotenes, whereas AMO-1618 increased the levels of all carotenes in all the strains. The wild type and mutants responded differently to the presence of streptomycin and beta-ionone. The possible mode of action of the above agents on carotenoid biosynthesis is discussed.